BAUHAUS AWAL SEKOLAH DESAIN - Asidigisianti Surya Patria (Universitas Trisakti, 2013)
AbstractBauhas is one of school of design in Germany which combine between art and craft. It was found by Walter Gropius who was and German Architect. Although Bauhas was only last for 15 years ( 19-19-1933) , it has huge impact to design and architecture. Besides the Bauhas artwork broke through the existing design inhtat period of time, the published book are used in school of design around the world. even the international style such as simple and use primery color also geometric shape become the part of modern design. The learning philosophy is also used until now which is learning by doing through studio system and workshop in school of design AbstrakBauhaaus adalah sekolah desain pertama di Jerman yang menyatukan anatara seni dan kriya . Didirikan oleh Walter Gropius seoranh arsitek Jerman. Meskipun hanya berdiri selama 15 tahun ( 1919-1933) pengaruhnya besar terhadap desain dan arsitektur. Selain karya-karya yang dihasilkan mendobrak rancangan yang telah ada, buku-buku yang dipublikasikan juga menjadi acuan sekolah-sekolah desain seluruh dunia. Bahkan gaya yang dinaut, seperti sederhana dan menggunakan warna primer serta bentuk geometris tetap menjadi acuan desain modern. Bhakan filosofi embelajarannya juga diterapkan hingga kini, yaitu learning by doing melalui sistem studio dan bengkel kerja di sekolah-sekolah